Artificial photosynthesis dendrimers integrating light-harvesting, electron delivery and hydrogen production1. Issue 24 (28th June 2015) - Xun, Zhiqing; Yu, Tianjun; Zeng, Yi; Chen, Jinping; Zhang, Xiaohui; Yang, Guoqiang; Li, Yi
<x xml:space="preserve">Abstract</x> Artificial photosynthesis dendrimers, which integrate light-harvesting, electron delivery and hydrogen production, were constructed and have demonstrated improved photocatalytic activity due to the dendritic architecture.